2006
DOI: 10.1021/ma0509964
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reorganization of an Amphiphilic Block Copolymer Film Studied by NEXAFS Spectroscopy

Abstract: The chemical composition of the surface of an amphiphilic diblock copolymer film, comprised of polystyrene and poly(4-(2-(2-(2-acetoxy)ethoxy)ethoxy)styrene), has been characterized upon equilibration in water and in a vacuum, employing surface sensitive near-edge X-ray absorption fine structure spectroscopy. The outermost surface layer exhibits a reversible exchange between the hydrophilic and hydrophobic polymer segments as the equilibrating interface is changed between water and vacuum, respectively. Surpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
(33 reference statements)
1
24
0
Order By: Relevance
“…Previously, we have employed X-ray absorption spectroscopy to investigate the chemical composition of the surface of thin films of the block copolymer PS-b-PAEES and its evolution upon equilibration in a wet or dry environment. 28 Similar work has been done for a copolymer with PEGylated and fluoroalkyl side chains. 35 We showed that alternating equilibration leads to a reproducible, essentially complete exchange of the molecular blocks composing the surface layer of the film; from hydrophilic PAEES blocks after water equilibration to hydrophobic PS blocks after vacuum equilibration and vice versa.…”
Section: Full Papermentioning
confidence: 86%
See 1 more Smart Citation
“…Previously, we have employed X-ray absorption spectroscopy to investigate the chemical composition of the surface of thin films of the block copolymer PS-b-PAEES and its evolution upon equilibration in a wet or dry environment. 28 Similar work has been done for a copolymer with PEGylated and fluoroalkyl side chains. 35 We showed that alternating equilibration leads to a reproducible, essentially complete exchange of the molecular blocks composing the surface layer of the film; from hydrophilic PAEES blocks after water equilibration to hydrophobic PS blocks after vacuum equilibration and vice versa.…”
Section: Full Papermentioning
confidence: 86%
“…For example, Senshu et al investigated the structural ordering under wet and dry conditions of poly(2‐hydroxyethyl)methacrylate‐ block ‐polyisoprene and poly(2‐hydroxyethyl)methacrylate‐ block ‐polystyrene interfaces by contact angle and transmission electron microscopy measurements. Morphology and chemical composition of the surface of thin amphiphilic diblock copolymer films have also been intensively studied in the past. Less is known, however, about the interplay between bulk order and surface properties and their respective influence on each other.…”
Section: Introductionmentioning
confidence: 99%
“…NEXAFS measurements allowed it to detect the surface reconstruction associated with this perturbation by detecting the functional groups exposed at the surface. [10] The block copolymers originally investigated for this purpose [9] had rather high T g -values. Thus, a solvent was necessary to reduce the T g of the hydrophilic block composed of hydroxystyrene by swelling.…”
Section: Full Papermentioning
confidence: 99%
“…We could also show the change in the chemical composition of the surface during the reconstruction process of a thin film of P4-block-P3 by surface-sensitive NEXAFS spectroscopy. [10] An example of such a surface reconstruction process in contact with water is shown for a thin film of P1-block-P4-2 in Figure 3. In this case a thin film (about 150 nm) of the block copolymer was spin-coated on a silicon wafer.…”
Section: General Partmentioning
confidence: 99%
“…However, no direct information regarding surface chemical composition is obtained by these techniques. Some groups currently use the near‐edge X‐ray absorption fine structure spectroscopy technique (NEXAFS) to investigate surface reconstruction of prehydrated surfaces in vacuum environment 10–12. This technique is very surface‐sensitive but requires access to a synchrotron light source.…”
Section: Introductionmentioning
confidence: 99%